2014
DOI: 10.1186/bf03353305
|View full text |Cite
|
Sign up to set email alerts
|

Seismic cycle on a strike-slip fault with rate- and state-dependent strength in an elastic layer overlying a viscoelastic half-space

Abstract: A numerical simulation of seismic cycles is performed using a two-dimensional model with a vertical strike-slip fault in an elastic layer overlying a Maxwellian viscoelastic half-space, where the frictional stress on the fault is assumed to obey a rate-and state-dependent friction law. Simulated seismic cycles in the viscoelastic Earth model are nearly the same as those in a uniform elastic half-space model. The simulated postseismic deformation on the Earth's surface due to viscoelastic relaxation is signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…It was also shown that the simulation predicts occurrence of a large postseismic slip on the plate interface, though viscoelasticity is not included in the model. In fact, Kato (2002) showed that a simulation for a case of a strike-slip fault embedded in a viscoelastic earth model gives almost the same results as those performed using a uniform elastic half-space model. Kato and Hirasawa (2000), based on a 2-D simulation model, evaluated effects of outer rise earthquakes on a seismic cycle of large interplate earthquakes by considering stress perturbation to the coupling region.…”
Section: Introductionsupporting
confidence: 52%
“…It was also shown that the simulation predicts occurrence of a large postseismic slip on the plate interface, though viscoelasticity is not included in the model. In fact, Kato (2002) showed that a simulation for a case of a strike-slip fault embedded in a viscoelastic earth model gives almost the same results as those performed using a uniform elastic half-space model. Kato and Hirasawa (2000), based on a 2-D simulation model, evaluated effects of outer rise earthquakes on a seismic cycle of large interplate earthquakes by considering stress perturbation to the coupling region.…”
Section: Introductionsupporting
confidence: 52%
“…These effects should be evaluated by using half‐space models [e.g., Hori et al , 2004]. Moreover, the effect of viscoelasticity should be included in future models to properly account for long‐term crustal deformation data [e.g., Kato , 2002]. (2) Smaller scale heterogeneity was neglected in the present model.…”
Section: Discussionmentioning
confidence: 99%
“…While finite-element modeling has proven versatile for forward and inverse modeling, notably using the adjoint method (Agata et al, 2017;Crawford et al, 2016), resolving the details of fault dynamics with this technique requires out-of-the-ordinary numerical resources and methods (Agata et al, 2014;Ichimura et al, 2016;Uphoff et al, 2017). While elegant, this approach is limited to linear viscoelastic properties and often to vertical stratification of material properties and ignores the coupling to brittle deformation, except for the work of N. Kato (2002). While elegant, this approach is limited to linear viscoelastic properties and often to vertical stratification of material properties and ignores the coupling to brittle deformation, except for the work of N. Kato (2002).…”
Section: Subduction Dynamics With the Integral Methodsmentioning
confidence: 99%
“…Viscoelastic simulations have also exploited the correspondence principle, whereby heterogeneous effective elastic properties are mapped into the viscoelastic properties by virtue of the Fourier or Laplace transforms (Chanard et al, 2018;Fukahata & Matsu'ura, 2006;Pollitz, 1992Pollitz, , 1997Smith & Sandwell, 2004). While elegant, this approach is limited to linear viscoelastic properties and often to vertical stratification of material properties and ignores the coupling to brittle deformation, except for the work of N. Kato (2002). Meanwhile, fault dynamics is efficiently simulated with the boundary-integral method (Ando, 2018;Lapusta & Liu, 2009;Y.…”
Section: Subduction Dynamics With the Integral Methodsmentioning
confidence: 99%